An Emissions Inventory for the City of Thessaloniki - Tsilingiridis, George; Zachariadis, Theodoros; Samaras, Zissis; Chantzaridou, A. (My University, 2001)
Recently, an advanced air quality management system has been implemented in the Organization for the Master Plan Implementation and Environmental Protection of Thessaloniki, that gives the possibility to the Organization to perform an efficient environmental planning regarding the city’s air quality. The paper presents the new detailed emission inventory with a high spatial and temporal resolution, for the major area of Thessaloniki for 1995. It is also presented the set of emission reduction scenarios developed to estimate the evolution of the air pollution levels in relation to structural changes and/or land-planning as well as the efficiency assessment of various air pollution abatement measures.